2021
DOI: 10.1111/jcmm.16347
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cell‐derived exosomal MicroRNA‐486‐5p regulates differentiation of spermatogonial stem cell through PTEN in mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The observations of Li et al 2021 about Sertoli cell miR-486-5p containing exosomes adds to the evolving school of thought on how undifferentiated spermatogonia enter meiosis ( 54 ). Spermatogonial differentiation and meiotic entry is established to be highly dependent on retinoic acid (RA) signaling ( 55 , 56 ).…”
Section: Endocrine and Paracrine Signalsmentioning
confidence: 93%
See 2 more Smart Citations
“…The observations of Li et al 2021 about Sertoli cell miR-486-5p containing exosomes adds to the evolving school of thought on how undifferentiated spermatogonia enter meiosis ( 54 ). Spermatogonial differentiation and meiotic entry is established to be highly dependent on retinoic acid (RA) signaling ( 55 , 56 ).…”
Section: Endocrine and Paracrine Signalsmentioning
confidence: 93%
“…Paracrine signaling from Sertoli to germ cells by exosomes containing microRNA would putatively be to silence genes. Indeed, a recent report by Li et al 2021, revealed that Sertoli exosomes contain the microRNA miR-486-5p ( 54 ). The authors used a culture system of adult Sertoli cells and P6 germ cells enriched for spermatogonial stem cells.…”
Section: Endocrine and Paracrine Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-34c promotes SSC differentiation by inhibiting the function of the NANOS2 gene, leading to the up-regulation of meiotic-related proteins, STRA8, in mice ( 56 ). Similarly, miR-486-5p secreted by Sertoli cells stimulates differentiation of SSCs in mice by up-regulating the expression of STRA8 and SYCP3 ( 57 ). Further, impaired spermatogenesis is observed in mice carrying a deficiency in miR-17-92 or a gene deletion of miR-17-92 ( 58 , 59 ).…”
Section: Regulation Of Sscsmentioning
confidence: 99%
“…Another non-coding RNAs, miRNAs, are members of endogenous small RNA with the length of about 18–24 nucleotides, involved in the regulation of mRNA expression. By binding to the 3′-untranslated region, miRNAs block the translation or induce the degradation of the target mRNA, thus modulating cell differentiation, growth, proliferation and apoptosis ( Li et al, 2021 ; Mohammadi et al, 2021 ; Xiang et al, 2021 ). miRNAs have been reported as diagnostic markers and therapeutic targets for the control of diseases ( Broermann et al, 2020 ; Tombolan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%